Is there a Need to Change the Basic Principles of Histology? Educational, Functional and Embryological Perspective - Varga, I; Kachlík, D; Csöbönyeiová, M; Feitscherová, C; Klein, M (Physiological research, 2022)
Although it is not an easy task to classify cells into different types, or in turn cell types into tissue types, a clear, understandable, didactically and clinically relevant tissue classification is indispensable for undergraduate medical education, expert discussions in biomedical research as well as for clinical practice. From the earliest discovery of the light microscope on, tissue classification has been a dynamic process. Historically, it was not a rare occurrence that different textbooks offered different tissue classifications. Nowadays, classifications have almost become uniform - the most common is the histological classification into four basic tissue types (epithelial, connective, muscle, nervous), which is recognized by the majority of modern histology and pathology textbooks. The reason is that, with some exceptions, this classification seems to be the most relevant not only for educational purposes but also from an embryological perspective and clinical-histopathological practice. Recently, attempts have been made to abandon this established classification and replace it with a new one. Any new classification, which would improve the presently used is welcomed. However, if the proposed innovation does not satisfy the needs of modern education and clinical practice, it should be handled with great caution or reconsidered.